KAUSALITAS ANTARA FUNDAMENTAL EKONOMI DAERAH DAN PERAN WANITA DALAM PEMBANGUNAN - Pujiati, Amin (Universitas Muhammdaiyah Surakarta, 2012)
This study aims to analyze the role of women in development and the causality between regional economic fundamentals and the role of women at Central Java. It uses district level data and supplied by the Indonesian Central Bureau of Statistics during 2001- 2009. The tools of analysis Granger Causality Test. The results of the analysis of the role of women in development is still low, from education, health, womens role and potential of public sector point of view. The Granger Causality tests results shows that a direct relationship between womens role in regional development with economic fundamentals, that also the role of women in development increased, causing increased local economic fundamentals. In this study there is no reciprocal relationship between economic fundamentals and the role of women.